Sport-related concussive convulsions: a systematic review - Kuhl, N. O.; Yengo-Kahn, A. M.; Burnette, H.; Solomon, G. S.; Zuckerman, S. L. (The Physician and Sportsmedicine, 2018)
Objectives: The incidence of sport-related concussion (SRC) continues to rise. Presentations of concussed athletes vary from subtle symptoms to notable signs. Between the 4th and 5th iterations of the Concussion in Sport Group (CISG) guidelines, concussive convulsions were removed as a modifying factor, but little evidence or discussion supported this change. While considerable research exists regarding post-traumatic epilepsy in moderate to severe traumatic brain injury, convulsions following SRC are relatively understudied. There is no clear consensus on the prevalence of convulsions, seizures, or the management of these entities following SRC. The aim of this review was to assess the state of the literature, describe the management trends of concussive convulsions and post-traumatic epilepsy in the SRC population, and provide evidence and guidance for the management of these athletes.